Analysis of the clinical manifestations and 18F-FDG PET-CT findings in 40 patients with histiocytic necrotizing lymphadenitis. Issue 35 (3rd September 2021) - Zhang, Rui; Liang, Lidan; Li, Daoming; Bai, Yuling; Li, Xiangzhou
Abstract : Abstract: Histiocytic necrotizing lymphadenitis (HNL) is a rare, benign, and self-limiting inflammatory disease that mainly involves the lymph nodes. There is a lack of large sample studies concerning the clinical manifestations and imaging features of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) of HNL. The clinical symptoms, laboratory examination results, 18F-FDG PET/CT imaging features, and treatment outcome were investigated in this retrospective study. A total of 40 HNL patients were recruited. The onset age was between 14 and 65 years, with a median of 25 years. The white blood cell count was 3.9 (2.9, 7.1) × 10 9 /L, C-reactive protein level was 20.2 (6.6, 63.8) mg/L, erythrocyte sedimentation rate was 29.0 (18.0, 45.0) mm/h, and ferritin was 616.5 (205.6, 2118.1) ng/mL. An abnormal liver function was observed in 23 patients. 18F-FDG PET-CT showed that an abnormal lymph node metabolism was observed in 38 patients, among which the highest 18F-FDG maximal standard uptake value (SUVmax) of the lymph nodes ranged between 3.4 and 41.9; the nodes were mainly distributed in the neck and axilla regions. Meanwhile, a total of 2502 lymph nodes (721 lymph nodes with a short axis greater than 10 mm) were found in the 38 patients, including 1837 lymph nodes with an 18F-FDG SUVmax ≥ 2.5. The 18F-FDG SUVmax of the spleen ranged from 2.5 to 9.2 in 20 patients, while that of central and peripheral bone marrow ranged from 2.7 to 36.0 in 30 patients. After follow-up for an average period of 1 month, the symptoms improved after prednisone treatment. HNL often occurs in adolescents. Scanning with 18F-FDG PET/CT showed that most patients had multiple involved lymph nodes that were hypermetabolic, and only few lymph nodes are enlarged. Besides, the spleen or central and peripheral bone marrow could sometimes be hypermetabolic. Glucocorticoid treatment for the HNL patients is effective.